2017
DOI: 10.1007/s10865-017-9863-x
|View full text |Cite
|
Sign up to set email alerts
|

Drinking and exercise behaviors among college students: between and within-person associations

Abstract: Prior work has suggested a paradoxical positive relationship between the risk behavior alcohol use and the health behavior exercise, particularly in young adults. Though seldom tested, different theoretical perspectives exist on the mechanisms that may explain the positive relationship. The aims of this study were to test theorized mechanisms of association, including common causes shared by both behaviors (e.g., personality, motives, affective), compensatory processes such as exercising to compensate for calo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 76 publications
1
22
0
1
Order By: Relevance
“…On the other hand, as alcohol consumption strongly associates with sport culture and sports events [81] and group drinking activity is perceived as the bonding activity among athletes [82], the positive association between alcohol consumption and exercise seems acceptable. Our findings on the association between alcohol consumption and exercise are also consistent with previous studies [83][84][85]. However, our finding that frequent gambling does not have a significant relationship with exercise is inconsistent with Håkansson et al [86], who found a positive association between problem gambling and physical activity.…”
Section: Discussionsupporting
confidence: 88%
“…On the other hand, as alcohol consumption strongly associates with sport culture and sports events [81] and group drinking activity is perceived as the bonding activity among athletes [82], the positive association between alcohol consumption and exercise seems acceptable. Our findings on the association between alcohol consumption and exercise are also consistent with previous studies [83][84][85]. However, our finding that frequent gambling does not have a significant relationship with exercise is inconsistent with Håkansson et al [86], who found a positive association between problem gambling and physical activity.…”
Section: Discussionsupporting
confidence: 88%
“…9 Although largescale epidemiological studies have presented evidence that alcohol use increases during college while physical activity decreases, 3,5 there is a contradictory body of literature indicating that these two behaviors may be positively associated. [10][11][12][13][14] Indeed, a recent systematic review reported that seven out of the eight published studies that examined the association between alcohol use and physical activity in college students found evidence that the two health behaviors were positively related. 10 This association also appears to be stronger in men than women, and may depend on the intensity of the physical activity in question.…”
mentioning
confidence: 99%
“…On the other hand, the most popular perspective is that individuals engage in physical activity to compensate for alcohol-related caloric intake. 14,19 Indeed, recent work has demonstrated that the majority of college women (84%) reported being strongly motivated to engage in greater levels of physical activity to counteract the calories consumed from alcohol as a way of balancing themselves out and maintaining an attractive figure. 13 Similarly, college men (76%) reported being motivated to engage in physical activity to balance out healthy and unhealthy behaviors with the hope that exercising can negate the adverse health effects of alcohol use.…”
mentioning
confidence: 99%
“…This association persists across age groups, levels of PA, and levels of drinking. Longitudinal studies examining within-person associations between alcohol use and PA have mixed findings, with findings indicating a positive [25,26], negative [27], or no association [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, common drinking motives include social, enhancement, coping, and conformity motives [14]. Understanding why individuals engage in golf may deepen researchers' understanding of associations between PA and alcohol use, particularly if both behaviors share underlying motivational origins [14,27]. The social nature of golf could also influence alcohol use [13].…”
Section: Introductionmentioning
confidence: 99%